Ice crystal-assisted intercalation of PANI within Ti3C2Tx MXene thin films for flexible supercapacitor electrodes with simultaneously high mechanical strength and rate performance. Issue 3 (3rd January 2023) - Wang, Jianhua; Jiang, Degang; Zhang, Maozhuang; Sun, Yuesheng; Jiang, Mingyuan; Du, Yiqi; Liu, Jingquan
Abstract : Ti3 C2 T x MXene thin-film electrodes are promising for flexible and wearable energy storage devices. Abstract : Ti3 C2 T x MXene thin-film electrodes are promising for flexible and wearable energy storage devices. Meanwhile, the restacking of MXene nanosheets largely affects their electrochemical properties when processing them into freestanding films. Introducing interlayer spacers can effectively eliminate this restacking problem; however balancing the restacking and mechanical strength of these films remains challenging. Here, an efficient strategy that utilizes ice crystals to help intercalate aniline monomers into a pre-frozen hydro-MXene film, followed by an in situ polymerization, is proposed. The ice crystals grown within the hydro-film significantly enlarge the interlayer space, facilitating the intercalation of aniline monomers dispersed into the MXene film. By minimizing the polyaniline (PANI) loading (0.6 wt%), the resultant PANI/MXene film shows both high mechanical strength (∼47 MPa) and electrochemical performances including a high volumetric capacitance of 1360 F cm −3 (gravimetric capacitance of 385 F g −1 ), rate performance (53.5% even at an ultrahigh scan rate of 10 V s −1 ) and stable cycling stability with 96.4% capacitance retention after 10 000 cycles. Moreover, the assembled supercapacitor device demonstrates good structural stability and flexibility under different bending tests. Thus, this work provides an efficient approach for fabricating MXene based thin films with a good balance of mechanical strength and electrochemical performances.